2001
DOI: 10.1177/107769900107800202
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Routine Forces in Gatekeeping

Abstract: Lewin's concept of “force” is explored in this study, which shows support for the proposition that newspaper gatekeeping is influenced more by forces on the routine level of analysis than by individual staff writers' characteristics. Newspaper stories about fifty Congressional bills were content analyzed, and two surveys were conducted of the stories' writers and of editors at their newspapers. No individual-level force was related to the quantity of coverage the bills received, whereas editors' aggregated ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
198
1
10

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(214 citation statements)
references
References 2 publications
5
198
1
10
Order By: Relevance
“…This study did address the impact of reporters' institutional work roles on source choice, which other researchers have found to be more important than reporters' personal characteristics in making such selections. This study's findings did not support the idea that work-roles influence the ways in which reporters fulfill their job duties, including their choice of information sources (Clark & Illman, 2003;Craft & Wanta, 2004;Dunwoody, 1978Dunwoody, , 19791980;Holland, 2009;Kitzinger & Reilly, 1997;Logan, 2001;Shoemaker, Eichholz, Kim, & Wrigley, 2001), although such impact may be derived from sources' influence on reporters' agendas and frames. According to the research cited, source choices of science-specialty-beat reporters (reporters specializing in coverage of stories with significant science components) may reflect not just normal newsroom routines and practices or individual reporter characteristics, but may be influenced by such reporters' special position within the news organization, by their special training, and by the narrative and expositional demands of the subject matter covered.…”
Section: Researchcontrasting
confidence: 50%
See 3 more Smart Citations
“…This study did address the impact of reporters' institutional work roles on source choice, which other researchers have found to be more important than reporters' personal characteristics in making such selections. This study's findings did not support the idea that work-roles influence the ways in which reporters fulfill their job duties, including their choice of information sources (Clark & Illman, 2003;Craft & Wanta, 2004;Dunwoody, 1978Dunwoody, , 19791980;Holland, 2009;Kitzinger & Reilly, 1997;Logan, 2001;Shoemaker, Eichholz, Kim, & Wrigley, 2001), although such impact may be derived from sources' influence on reporters' agendas and frames. According to the research cited, source choices of science-specialty-beat reporters (reporters specializing in coverage of stories with significant science components) may reflect not just normal newsroom routines and practices or individual reporter characteristics, but may be influenced by such reporters' special position within the news organization, by their special training, and by the narrative and expositional demands of the subject matter covered.…”
Section: Researchcontrasting
confidence: 50%
“…By extension, work by Shoemaker, Eichholz, Kim, and Wrigley (2001) and by Craft and Wanta (2004) suggests that (a) a newspaper's employing a science-specialty-beat reporter may go a long way toward determining the nature of its coverage of science-based news and (b) the unique position of a science-specialty-beat reporter in a newsroom could impact the quantity, type, and tone of science coverage provided. However, this study found no differences in source selection based on reporter…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to this challenge, media messages are often packaged into familiar and predictable forms, known as "media logic" or "medialization," which have proven successful in attracting the target audience's attention (37,38). Gatekeeping theory describes the upstream influences of organizational routines, external pressures, and internal goals of media industries that shape the messages and formats that eventually emerge for audience consumption (39,40). The theory emphasizes that news stories are not preexisting units that journalists merely select for transmission, but rather, reality becomes news through a selective structuring that creates units that fit the organizational needs, such as timing of creation, ease of transmission, and audience expectations.…”
Section: Mass Media and Narrativesmentioning
confidence: 99%